2002
DOI: 10.1063/1.1427920
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing motion of spherical particles in fluids

Abstract: We investigate experimentally the bouncing motion of solid spheres onto a solid plate in an ambient fluid which is either a gas or a liquid. In particular, we measure the coefficient of restitution e as a function of the Stokes number, St, ratio of the particle inertia to the viscous forces. The coefficient e is zero at small St, increases monotonically with St above the critical value Stc and reaches an asymptotic value at high St corresponding to the classical “dry” value emax measured in air or vacuum. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
322
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(369 citation statements)
references
References 28 publications
43
322
3
1
Order By: Relevance
“…Their model neglects the elastic deformation of the particles, which occurs over lengths comparable with the roughness height according to the elastohydrodynamics analysis in Davis et al (1986). The authors do not compare their results with the trajectory of a bouncing particle; however, they do compare with experimental measurements of the speeds of the particle before and after collision through the effective coefficient of restitution data from Gondret et al (2002). The recent work by Feng, Michaelides & Mao (2010) presents a collision model using a spring and dashpot, similar to softsphere collision models for dry granular flows.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Their model neglects the elastic deformation of the particles, which occurs over lengths comparable with the roughness height according to the elastohydrodynamics analysis in Davis et al (1986). The authors do not compare their results with the trajectory of a bouncing particle; however, they do compare with experimental measurements of the speeds of the particle before and after collision through the effective coefficient of restitution data from Gondret et al (2002). The recent work by Feng, Michaelides & Mao (2010) presents a collision model using a spring and dashpot, similar to softsphere collision models for dry granular flows.…”
Section: Introductionmentioning
confidence: 81%
“…Based on the measured temperature and apparent specific gravity, the concentration, density and viscosity of the mixture can be found from Dow Chemical Synthetic Glycerin Products. A typical value of the apparent specific gravity is 1.205 at 20 • C corresponding to a density of 1203 kg m −3 and a viscosity of 50.2 × 10 −3 Pa s. Gondret et al (2002) showed that the impact speed was not changing within this time interval in their experiments. Because of the small values of h(t = 0)/D, the particle does not achieve its terminal velocity before it contacts the wall.…”
Section: Materials Propertiesmentioning
confidence: 93%
See 3 more Smart Citations